Serum periostin in obstructive airways disease. Issue 5 (25th February 2016) - Fingleton, James; Braithwaite, Irene; Travers, Justin; Bowles, Darren; Strik, Rianne; Siebers, Rob; Holweg, Cecile; Matthews, John; Weatherall, Mark; Beasley, Richard
Serum periostin is a potential biomarker of response to therapies that target type 2 inflammation in asthma. The objectives of this study were to describe: 1) the distribution of serum periostin levels in adults with symptomatic airflow obstruction; 2) its relationship with other variables, including type 2 biomarkers; and 3) the effect of inhaled corticosteroids on periostin levels. Serum periostin levels were measured in a cross-sectional study exploring phenotypes and biomarkers in 386 patients aged 18–75 years who reported wheeze and breathlessness in the past 12 months. In 49 ICS-naïve patients, periostin levels were measured again after 12 weeks of budesonide (800 μg·day −1 ). The distribution of serum periostin levels was right skewed (mean±sd 57.3±18.6 ng·mL −1, median (interquartile range) 54.0 (45.1–65.6) ng·mL −1, range 15.0–164.7 ng·mL −1 ). Periostin was positively associated with exhaled nitric oxide (Spearman's rho=0.22, p<0.001), blood eosinophil count (Spearman's rho=0.21, p<0.001), and total IgE (Spearman's rho=0.14, p=0.007). The Hodges–Lehmann estimator (95% CI) of change in periostin level after ICS therapy was −4.8 (−6.7– −3.2) ng·mL −1 (p<0.001). These findings provide data on the distribution of serum periostin in adults with symptomatic airflow obstruction, the weak associations between periostin and other type 2 markers, and the reduction in periostin with inhaled corticosteroid therapy. Serum periostin levels may be a distinct marker of type 2 inflammation in adults with symptomatic airways disease http://ow.ly/XAKyK